2006
DOI: 10.3348/kjr.2006.7.3.193
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Follow-up US Evaluation of Ruptures of the Medial Head of the Gastrocnemius ("Tennis Leg")

Abstract: ObjectiveThe purpose of this study was to demonstrate the ultrasonographic (US) findings of rupture and the healing process of the medial head of the gastrocnemius ("Tennis Leg").Materials and MethodsTwenty-two patients (age range: 30 to 45 years) with clinically suspected ruptures of the medial head of the gastrocnemius were referred to us for US examination. All the patients underwent US of the affected limb and the contralateral asymptomatic limb. Follow-up clinical evaluation and US imaging of all patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
67
1
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(73 citation statements)
references
References 13 publications
1
67
1
4
Order By: Relevance
“…Speaking of the size of the lesion, Kwak et al 16 reported that the largest dimension of the liquid collection after injury in the gastrocnemius muscle was 125mm 16 while we found the collections sized up to 52mm. Previous research by the same group reported larger diameter of liquid collections 17 .…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…Speaking of the size of the lesion, Kwak et al 16 reported that the largest dimension of the liquid collection after injury in the gastrocnemius muscle was 125mm 16 while we found the collections sized up to 52mm. Previous research by the same group reported larger diameter of liquid collections 17 .…”
Section: Discussioncontrasting
confidence: 40%
“…Also, none of the patients were hospitalized and all of them were treated conservatively. Kwak et al 16 underlines in his paper that all of the patients with rupture of the medial head of the gastrocnemius muscle were hospitalized for one to four days. In our research we found that all patients were treated with different types of immobilization regardless of the type of lesion.…”
Section: Discussionmentioning
confidence: 99%
“…The most common mechanism of rupture is dorsiflexion of the ankle with knee in full extension which results in simultaneous active contraction and passive stretching of the muscle 2. It is very common in tennis players and hence the term ‘tennis leg’ was coined by Powell3.…”
Section: Discussionmentioning
confidence: 99%
“…Most authors recommend the use of rest, ice, compression and elevation immediately following injury followed by passive stretching exercises and isometric strengthening rehabilitation until full intensity sports can be resumed [11,12] . Ultrasound follow-up has even demonstrated primary union at the rupture site, taking place as early as 4 weeks after the initial injury, following conservative measures only [13] . Cases of surgical management of tennis leg are scarce within the literature.…”
Section: Discussionmentioning
confidence: 99%